Envisioning democracy : new essays after Sheldon Wolin's political thought - Maley, Terry; Wallach, John R. (University of Toronto Press, 2023)
"There is no political term today that has a greater cachet and so little clarity than democracy. Leaders of large states use it to designate their nations' public character, while it is also used by critics of leaders calling themselves "democratic" to spearhead their calls for political reforms. In Envisioning Democracy, Terry Maley and John R. Wallach address the following key questions: What does democracy mean today? What could it mean tomorrow? What is the dynamic of democracy, especially in an increasingly interdependent world of growing inequality, that can be captured by authoritarian populist leaders? Envisioning Democracy explores these questions amid the dynamic of democracy as a political phenomenon interacting with forms of economic, ethical, and intellectual life. The book draws on the thought of one of America's greatest writers on democracy in the last fifty years, Sheldon S. Wolin (1922-2015). In this collection, scholars consider the historical conditions, theoretical elements, and practical impediments to democracy, relying on Wolin's insights as touchstones in thinking through what democracy means now and what it could mean in the future. Envisioning Democracy presents new perspectives on longstanding, current, and future issues surrounding democracy and liberalism in political theory."--